Best technique for fixation of displaced transverse olecranon fractures: tension band wiring or plate fixation? - Yogi, Lokesh Kumar; Mahi, Gagandeep; Thorat, C. R.; Naik, Moti Janardhan (International Journal of Research in Orthopaedics, 2020)
Background: Fractures of olecranon are common fractures in upper limb. Tension band wiring (TBW) and plate fixation (PF) are mostly used techniques but choice is based on type of fracture and surgeon’s preference. Methods: A study assessed functional results in 28 patients that were enrolled after the clinical event of trauma has occurred. Patients were divided into two groups- Group (A) for TBW and Group (B) for PF; here gender, age and side of fracture were ignored. Post-operative functional outcome were evaluated by using the Mayo Elbow Performance (MEP) and the Disabilities of the Arm, Shoulder and Hand (DASH) score parameters. Results: Mean (SD) union time as determined by postoperative radiographs was 8.5 (1.48) weeks for group (A) and 9 (2.08) weeks for group (B). Mean (SD) MEP score at 9 months in group (A) 84.28 (7.28) and 80.71 (10.92) in group (B). Mean (SD) DASH at 9 months in group (A) 12.2 (8.8) and 11.7 (10.4) in group (B). Complications were reported in group (A) 6 patient (42.85%) out of 14 patients and in group (B) 1 patient (7.14%) out of 14 patients. Conclusions: The current study shows that there are no significant differences in functional outcome between both the study groups. Due to lesser complications, we recommend the plate fixation approach as the better choice for transverse displaced olecranon fractures. More large scale studies are required to further confirm our results.